2005
DOI: 10.1097/01.tp.0000156319.47645.3b
|View full text |Cite
|
Sign up to set email alerts
|

Intrasplenic Transplantation of Encapsulated Hepatocytes Decreases Mortality and Improves Liver Functions in Fulminant Hepatic Failure from 90% Partial Hepatectomy in Rats

Abstract: The intrasplenic transplantation of cultured encapsulated hepatocytes improved the survival rate of an acute liver failure rat model induced by a 90% partial hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 30 publications
3
28
0
1
Order By: Relevance
“…Application of cells in patients with decompensated chronic liver disease has resulted in some improvement of laboratory parameters, but was not able to change the natural cause of the disease (Ott M., unpublished). Encapsulation of hepatocytes [4,62] or their attachment to microcarriers may be an alternative method to improve efficacy of intraperitoneal cell transplantation. Implantable hepatocyte-based devices may represent another alternative for the treatment of end-stage liver disease [10].…”
Section: End-stage Liver Disease (Cirrhosis)mentioning
confidence: 99%
“…Application of cells in patients with decompensated chronic liver disease has resulted in some improvement of laboratory parameters, but was not able to change the natural cause of the disease (Ott M., unpublished). Encapsulation of hepatocytes [4,62] or their attachment to microcarriers may be an alternative method to improve efficacy of intraperitoneal cell transplantation. Implantable hepatocyte-based devices may represent another alternative for the treatment of end-stage liver disease [10].…”
Section: End-stage Liver Disease (Cirrhosis)mentioning
confidence: 99%
“…Thus, the specific culture conditions and the 3D hepatocyte structure appeared to enable the hepatocytes to retain their viability and to increase function. The previous study showed that microencapsulated hepatocytes survived for at least 21 days under culture conditions, and surprisingly, improved their hepatic function during the 7 days after cultivation [19] . Microencapusle cell might increase the contact chance between the cells.…”
Section: Protein Secretion Of Microencapsulated Cellsmentioning
confidence: 98%
“…HTx has been studied in laboratory settings for approximately three decades [7][8][9][10], and Mito et al [11] reported the first performance of HTx clinically in the early 1990s. Since then, many researchers have proposed HTx as a treatment for metabolic liver diseases or as a bridge to OLTx in patients with fulminant liver failure [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%